(untitled) (Discourse of Law and Administration, 2023)
The system of reaction for a misdemeanor shows many specificities compared to the system of reaction for a crime, fiscal offense and fiscal misdemeanor. The legislator, apart from such traditional means of reaction for a misdemeanor as a penalty or a penal measure, provides for educational and social impact measures. The study analyzes one of the institutions traditional and characteristic of substantive offense law, which is the institution of social impact measures. Social impact measures have been in force basically unchanged for 50 years. This leads to the question of whether maintaining the normative regulation shaping social impact measures in its current form is still justified and to assess from the point of view of the effectiveness of preventing and combating offences, as well as assessing compliance with the basic guarantee principles of the substantive law of offenses. Against this background, the following were analysed: normative nature, functions, objectives, premises for use, catalogue, content of individual social impact measures, mode and manner of their implementation.